NON-ALCOHOLIC FATTY LIVER DISEASE, MODERN VIEWS (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article presents the literature about the problem of non-alcoholic fatty liver disease, which is a polyetiological disease. Excessive consumption of foods rich in fats and carbohydrates leads to the release of large amounts of free fatty acids (FFA) from the gastrointestinal tract into the blood and further into the liver, resulting in the development of steastosis. Inflammatory mediators actively released by adipose tissue directly damage hepatocyte membranes, which leads to the accumulation of fibrous tissue in the liver. The main feature of this disease is that it is often asymptomatic and is diagnosed accidentally on the basis of laboratory or instrumental studies performed in patients with metabolic syndrome. Being a very common pathology, non-alcoholic fatty liver disease requires a thorough study of the mechanisms of its pathogenesis and the search for the most optimal non-invasive methods for identifying and assessing its complex forms (steatohepatitis, fibrosis, cirrhosis).